Performance of a rapid immuno-chromatographic test (Schistosoma ICT IgG-IgM) for detecting Schistosoma-specific antibodies in sera of endemic and non-endemic populations. - Julie Hoermann; Esther Kuenzli; Carmen Schaefer; Daniel H Paris; Silja Bühler; Peter Odermatt; Somphou Sayasone; Andreas Neumayr; Beatrice Nickel (Public Library of Science (PLoS), 2022)
Background Schistosomiasis, an acute and chronic parasitic disease caused by human pathogenic Schistosoma species, is a neglected tropical disease affecting more than 220 million people worldwide. For diagnosis of schistosomiasis, stool and urine microscopy for egg detection is still the recommended method, however sensitivity of these methods is limited. Therefore, other methods like molecular detection of DNA in stool, detection of circulating cathodic antigen in urine or circulating anodic antigen in urine and serum, as well as serological tests have gained more attention. This study examines the sensitivity and specificity of a rapid diagnostic test based on immunochromatography (Schistosoma ICT IgG-IgM, LD Bio, Lyon, France) for simultaneous detection of specific IgG and IgM antibodies in serum, against Schistosoma spp. in endemic and non-endemic populations. Methodology/principal findings Frozen banked serum samples from patients with confirmed schistosomiasis, patients with other helminth infections, patients with seropositive rheumatoid arthritis and healthy blood donors were used to assess the sensitivity and the specificity of the Schistosoma ICT IgG-IgM rapid diagnostic test. The test showed a sensitivity of 100% in patients with parasitologically confirmed schistosomiasis, irrespective of the species (S. mansoni, S. haematobium, S. japonicum, S. mekongi). In healthy blood donors and patients with rheumatoid factor positive rheumatoid arthritis from Europe, specificity was 100%. However, in serum samples of patients with other tissue invasive helminth infections, the test showed some cross-reactivity, resulting in a specificity of 85%. Conclusion/significance With its high sensitivity, the Schistosoma ICT IgG-IgM rapid diagnostic test is a suitable screening test for detection of Schistosoma specific antibodies, including S. mekongi. However, in populations with a high prevalence of co-infection with other tissue invasive helminths, positive results should be confirmed with other diagnostic assays due to the test's imperfect specificity.